Implementasi Prinsip Accountability Dalam Pembiayaan Kegiatan Pendidikan di SD Negeri 1 Ketileng Todanan - Lutfia, Emi; Kurnia, Anora Wanodiya; Setyaningrum, Any Inti Wahyu; Nurkolis, Nurkolis (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine how the principle of accountability is applied in financing extracurricular scouting and dance activities at SD Negeri 1 Ketileng Todanan, Blora, and to identify factors that support or hinder the implementation of the principle. This study uses a field method with a qualitative descriptive approach. The data analysis process includes the stages of data reduction, data presentation, and drawing conclusions or verification. Based on the results of the study, it can be concluded that the implementation of the principle of accountability in financing scouting and dance activities at the school has been carried out well. All stages from planning, implementation, to financial reporting are carried out transparently, accountably, and involve various parties such as schools, committees, and parents of students. Factors that support the implementation of accountability include the existence of clear goals and objectives, a strong institutional structure, targeted policies, and detailed and appropriate planning. Meanwhile, the obstacles faced include a lack of understanding of accountability, the absence of competent administrative staff in financial management, and low participation from the School Committee and parents of students.